ANALYSIS OF THE ROLE OF NURSING CARE IN PROMOTING HEALTH FOR THE ELDERLY IN PRIMARY CARE (REMUNOM, 2025)
Population aging has led to changes in the demographic and epidemiological profile of Brazilian society. In this sense, health policies aimed at preventing diseases and health conditions have become frequent and relevant. In this scenario, the nurse, through their assistance, has an increasingly important role in relation to the elderly. This review article seeks to analyze the role of nursing care in promoting the health of the elderly in Primary Care. For the research, the "PICO" Strategy was used as a search and selection methodology, with the use of inclusion and exclusion criteria for results. For this purpose, the Virtual Health Library (VHL) portal was used, through the LILACS and BDENF (Nursing) databases, using the descriptors "nursing care", "elderly health" and "Primary Care". With this study, it was observed that nursing care is multifaceted, focusing on clinical care, health promotion and disease prevention, health conditions, as well as comprehensive and systematic monitoring of the elderly in Primary Care. Through these cares, the nursing professional can contribute to a healthier and more active aging, with quality of life.